2012
DOI: 10.1371/journal.pone.0045759
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Intra-Individual Variability in Simple and Choice Reaction Time: Systematic Review and Meta-Analysis

Abstract: BackgroundIntra-individual variability in reaction time (RT IIV) is considered to be an index of central nervous system functioning. Such variability is elevated in neurodegenerative diseases or following traumatic brain injury. It has also been suggested to increase with age in healthy ageing.ObjectivesTo investigate and quantify age differences in RT IIV in healthy ageing; to examine the effect of different tasks and procedures; to compare raw and mean-adjusted measures of RT IIV.Data SourcesFour electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
121
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 65 publications
17
121
2
1
Order By: Relevance
“…Paired associates learning (PAL) task and simple reaction time (SRT) task from the CANTAB battery were employed as measures of memory (visual–spatial) and reaction time, both of which are affected by advancing age (Der & Deary, 2006; Dykiert, Der, Starr, & Deary, 2012; Petersen, Smith, Kokmen, Ivnik, & Tangalos, 1992; Skolimowska, Wesierska, Lewandowska, Szymaszek, & Szelag, 2011; Sliwinski & Buschke, 1999). Computer expertise was not required to complete these tasks as responses were recorded via a touch screen (PAL) and a button box (SRT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paired associates learning (PAL) task and simple reaction time (SRT) task from the CANTAB battery were employed as measures of memory (visual–spatial) and reaction time, both of which are affected by advancing age (Der & Deary, 2006; Dykiert, Der, Starr, & Deary, 2012; Petersen, Smith, Kokmen, Ivnik, & Tangalos, 1992; Skolimowska, Wesierska, Lewandowska, Szymaszek, & Szelag, 2011; Sliwinski & Buschke, 1999). Computer expertise was not required to complete these tasks as responses were recorded via a touch screen (PAL) and a button box (SRT).…”
Section: Methodsmentioning
confidence: 99%
“…Following this, participants completed two assessment blocks of 50 trials each. As older age is associated with slowing of reaction times (Der & Deary, 2006; Dykiert et al., 2012; Woods, Wyma, Yund, Herron, & Reed, 2015), the outcome measure used to assess performance on this task was mean reaction time (RT).…”
Section: Methodsmentioning
confidence: 99%
“…Here, the extent to which attentional or executive processes are focused is reflected in RTs of differing duration with more consistent responding indicating greater focus. Across individuals, variability typically increases with age (Bielak, Cherbuin, Bunce, & Anstey, 2014;West et al, 2002), even when controlling for age-related slowing (Dykiert, Der, Starr, & Deary, 2012). Also, it has been proposed that RT variability is a behavioural marker of neurobiological disturbance (Hultsch et al, 2008) and consistent with this view, elevated variability has been shown to accompany neuropathology such as mild cognitive impairment or dementia (e.g., Duchek et al, 2009), Parkinson's disease (de Frias, Dixon, Fisher, & Camicioli, 2007), and traumatic brain injury (Stuss, Murphy, Binns, & Alexander, 2003).…”
Section: Does Within-person Variability Predict Errors In Healthy Adumentioning
confidence: 99%
“…It is well established that ageing is accompanied by cognitive decline and slowing of processing speed (e.g., Salthouse, 2010). However, an accumulating body of research suggests older adults are also more variable than younger adults (e.g., Bielak, Cherbuin, Bunce, & Anstey, 2014), even when response speed is taken into account (Dykiert, Der, Starr, & Deary, 2012). One proposal holds that IIV is an early indicator of neurobiological disturbance (Hultsch, MacDonald, Hunter, Levy-Bencheton, & Strauss, 2000;Hultsch, Strauss, Hunter, & MacDonald, 2008).…”
Section: Introductionmentioning
confidence: 99%